Dermatofibroma with Verocay Body-Type Palisading Features and a Brief Discussion on Potential Schwannoma Mimickers of the Skin - Yunus Baran KOK; Cuyan DEMIRKESEN (Federation of Turkish Pathology Societies, 2023)
Several types of cutaneous tumors can show palisading features or the so-called rippled pattern. The list includes adnexal tumors such as trichoblastoma and sebaceoma, basal cell carcinoma, leiomyoma, perineuroma, myofibroblastoma, and even malignant melanoma. Dermatofibroma, which is known for having a large variety of histological patterns, is also in the list. Here we present a case of dermatofibroma with palisading features strikingly similar to Verocay bodies of schwannoma.